An empirical model of the bulk shipping market - Lun, V.; Quaddus, Mohammed (Inderscience Publishers, 2009)
There are four markets in shipping, namely the freight market that trades sea transport, the second-hand market that trades used ships, the new building vessel market that trades new ships and the demolition market that deals with scrap ships. These four shipping markets are closely associated. This study aims to provide insights into the four shipping markets and to explain how these markets affect one another by empirically testing the relationships among the key variables of bulk shipping – prices of ships (in new building market, second-hand market and demolition market), fleet size, freight rate, and seaborne trade. The study results show that seaborne trade significantly affects fleet size, while fleet size is also affected by freight rate. On the other hand, freight rate has a significant impact on ship prices, i.e., new building, second-hand and scrap vessel prices. Based on the findings, a regression equation is developed to predict fleet size. Theoretical and practical implications of the bulk shipping market model are also discussed in this study.